1995
DOI: 10.1088/0953-8984/7/37/005
|View full text |Cite
|
Sign up to set email alerts
|

Prominent ferroelastic domain walls in BiVO4crystal

Abstract: The domain structure of ferroelastic BiVO4 crystals was investigated by X-ray diffraction, nuclear magnetic resonance, optical polarizing microscopy, transmission electron microscope, and electron diffraction techniques. From these results, it is found that the BiVO4 crystals have only prominent W walls and no non-prominent W' domain walls. A model of the twin structure is suggested, and all experimental results are explained in terms of this model. However, the prominent W wall obtained from our experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(93 citation statements)
references
References 25 publications
3
90
0
Order By: Relevance
“…Interest in the study of BiVO 4 was initially due to the ferroelastic properties of the material, and its ferroelastic-paraelastic transition reported at 528 K (255 • C) [18], a property that depends on the crystal structure. BiVO 4 has three main crystal forms: a monoclinic scheelite, a tetragonal zircon-type and a tetragonal scheelite structures [18,19].…”
Section: Bivo 4 As a Photoanodementioning
confidence: 99%
See 1 more Smart Citation
“…Interest in the study of BiVO 4 was initially due to the ferroelastic properties of the material, and its ferroelastic-paraelastic transition reported at 528 K (255 • C) [18], a property that depends on the crystal structure. BiVO 4 has three main crystal forms: a monoclinic scheelite, a tetragonal zircon-type and a tetragonal scheelite structures [18,19].…”
Section: Bivo 4 As a Photoanodementioning
confidence: 99%
“…Interest in the study of BiVO 4 was initially due to the ferroelastic properties of the material, and its ferroelastic-paraelastic transition reported at 528 K (255 • C) [18], a property that depends on the crystal structure. BiVO 4 has three main crystal forms: a monoclinic scheelite, a tetragonal zircon-type and a tetragonal scheelite structures [18,19]. An irreversible transition from the tetragonal zircon-type to the monoclinic scheelite structure occurs at calcination temperatures of about 400-500 • C. Moreover, a reversible transition occurs between the monoclinic-scheelite and the tetragonal scheelite structures at a temperature of 255 • C, the same temperature that is responsible for the ferroelastic-paraelastic transition.…”
Section: Bivo 4 As a Photoanodementioning
confidence: 99%
“…[7][8][9][10] Different synthetic routes leads to BiVO 4 in two crystalline phases: monoclinic (space group I2/b) and tetragonal (space group I4 1 /a) scheelite. 11,12 Among the above crystal phases, the monoclinic BiVO 4 is the best visible-lightdriven photocatalyst. The results reported by Yu et al demonstrated that the crystalline structure is the vital factor controlling MB degradation and O 2 evolution reactions.…”
Section: -6mentioning
confidence: 99%
“…[10][11][12] BiVO 4 is well-known for its ferroelastic properties 13 and its use as a nontoxic, bright yellow pigment 14,15 and has received some attention as a visible-light active photocatalyst. [16][17][18] The oxide has been synthesized by various means, including traditional solid state, [19][20][21] hydrothermal, 22,23 sonochemical, 24 and aqueous/coprecipitation. 16,25,26 With a bandgap of 2.4 eV, BiVO 4 absorbs well into the visible spectrum and has shown significant visible-light activity for O 2 evolution from AgNO 3 solutions, which act as the oxidizing agent.…”
Section: Introductionmentioning
confidence: 99%